PERANCANGAN BUKU MENGGAMBAR DAN MEWARNAI BERTEMA BATIK SEBAGAI MEDIA PEMBELAJARAN BATIK UNTUK ANAK USIA 4-6 TAHUN - Daru Anggara Murty; Sri Puji Astuti (LPPM Universitas Pekalongan, 2022)
Identity of Cultural heritage closely nations is batik. The impact of UNESCO is growth imitation technique, then decreasing batik producer in Pekalongan. To maintain and preserve batik is by inviting next generation. The design of book for children aged 4-6 years is expected to increase interest in batik as a learning medium. This research was conducted by observing analyzing previous drawing and coloring books. Conducted structured interviews with the Chairperson of the Indonesian Batik Craftsmen and Entrepreneurs Association (APPBI) and the Head of the Pekalongan service. and conduct unstructured interviews with children in kindergarten schools in Pekalongan and study the literature. The result of the concept of designing a drawing and coloring book refers to the learning media for children aged 4-6 years by lifting the classic solo-yogya batik motif. The discussion of the book is in the form of basic batik knowledge